PENERAPAN PSAK 109 TENTANG AKUNTANSI ZAKAT DAN INFAK/SEDEKAH PADA BAZ KOTA PEKANBARU - Devi Megawati Fenny Trisnawati (Kutubkhanah, 2015)
Zakat management organization (OPZ) in Indonesia is growing by leaps and bounds, even among OPZ competing for the collection of zakat, donation/charity to attract the sympathy of the Muslim community in particular muzakis and donors. Many ways to do that is by making the program amil zakat distribution of creative and innovative as mustahik economic empowerment so that the program can improve the status of mustahik (alms receivers) into a minimal muzakki munfiq (people who berinfak). But the important thing is the publication to the public as well as to implement transparency and accountability in the management of zakat. To the authors are interested to further investigate the application of SFAS 109, Accounting for Zakat, Infak/BAZ Alms in the city of Pekanbaru. Where BAZ Pekanbaru which has been confirmed by Walikota Pekanbaru since 2001, experienced a significant development in terms of the collection of zakat since last 2 years with a period of management the period 2011 till 2013. This study is a descriptive and comparative study between zakat management accounting practice in the field with the provisions of SFAS 109 . The results showed that the BAZ Pekanbaru has applied SFAS 109 on its financial reporting since 2011 are listed in the annual report 2011 and 2012. And the embodiment of transparency and accountability is a positive impact on the increase in the collection of zakat, donation/charity. And increase public confidence in government and the city of Pekanbaru